Percepções de um grupo de médicos residentes de clínica médica sobre cuidados paliativos em idosos hospitalizados - Marcolin, Daniel (2012)
The finitude of life issues, palliative care, care for the patient without therapeutic possibility are complex, comprehensive and still generate anxiety and anguish in the professionals. With increasing longevity, chronic diseases and technological development in the field of medicine and permanence of life, many older people live long, but at the cost of great suffering or poor quality of life when they are sick. The attitude of professionals is strongly influenced by experiences during training, and is no longer possible that the teaching has to be treated mechanically, or even technicalities. Dealing with the finitude and thus with death provides a look that emphasizes the importance of attitudes towards it. Thus, following the trend of global respect for human dignity, especially those that deal directly with patients without therapeutic possibility, a challenge for medical professionals and also to the caregivers, is that the study was conducted. Aimed to know the actions and relationships that underlie the approach and palliative care in the elderly, conducted by group of Resident Doctors of Medicine in a university hospital in Rio Grande do Sul specific objectives: to analyze the process of coping the death of an elderly patient terminal in medical practice, experienced by a group of Resident Doctors, to know the attitudes that these professionals have in front of an elderly patient out of treatment resources for healing, to investigate the training of resident physicians to approach and terminally ill patients who need palliative care, discover the leading reference of pipes and palliative care approach in the interpretation of the research group. Participants were fifteen residents in Internal Medicine at a teaching hospital in the state of Rio Grande do Sul Data were collected through semi-directed, recorded, held between February and August 2011. The individual interviews were held after signing the consent form. The study was approved by the Ethics Committee of the University of Passo Fundo, Opinion number, protocol number CAAE 0251.0.398.000-10. We used thematic analysis of Minayo (2004), building categories: experiences of professionals with patients beyond therapeutic possibilities, envisioning the formation; views of residents towards death and dying relationship of the physician and the family patient. It was noted how much is still difficult to treat the patient without therapeutic possibility for medical professionals who have many fears and doubts ahead to what the patient has, and especially by what is needing. This may reflect the approach that is little data on this subject at undergraduate level. Moreover, it was shown how the doctor-patient relationship and doctor-family is of paramount importance for better management of this patient and the decision-making ahead of palliative care. Thus, it was seen how much is an emerging reform in medical education in order to better prepare professional approach to the patient and family in the process of death and dying, thus minimizing the suffering involved, avoiding the installation of futility respecting the quality is more than just lifetime